Service Research and Innovation Third Australian Symposium, ASSRI 2013, Sydney, NSW, Australia, November 27-29, 2013, Revised Selected Papers - Davis, Joseph G.; Demirkan, Haluk; Motahari-Nezhad, Hamid R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed proceedings of the Third Australian Symposium on Service Research and Innovation, ASSRI 2013, held in Sydney, NSW, Australia, in November 2013. Overall, eight research papers were carefully reviewed and selected from 18 submissions. They are multidisciplinary in scope and cover strategic, organizational, and technological dimensions, ranging from purely conceptual to concrete implementations and testing of service-related technological platforms. Taken together, these papers provide a snapshot of the critical concerns and developments in service-related research and cover some of the key areas of research focus.
An RDR-Based Approach for Event Data Analysis -- Effective Governance During SOA Lifecycle - Theory and Practice -- Understanding a Transformation Process from Product-Centric to Customer-Centric Services in a Financial Institution - A Work System Perspective -- An Integrative Design Framework for New Service Development -- Smart CloudBench - Test Drive the Cloud Before You Buy -- A Six Cell Services Comparison Model for Healthcare -- Decisions, Models and Opportunities in Cloud Computing Economics: A Review of Research on Pricing and Markets -- Normative Requirements for Business Process Compliance.
Keywords: Business; Information technology; Business -- Data processing; Application software; Management information systems; Computer science; Business and Management; IT in Business; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems; Electronic books